Assessing the potential of nature-based solutions as sustainable land and water management strategies in the high tropical Andean páramo ecosystem - Fonseca, Kalina; Acero Triana, Juan S.; Ramírez, Miguel; Martínez, William; Ilbay, Mercy; Espitia-Sarmiento, Edgar; Breuer, Lutz; Justus Liebig University Giessen (My University, 2024)
Nature-based solutions (NbS) are gaining attention as viable strategies for restoring water-rich ecosystems such as the páramo. However, the lack of evidence on their effectiveness, coupled with a limited understanding of their political, economic, social, technological, environmental, and legal (PESTEL) context, hinders their widespread adoption. To address this gap, we propose a multi-method framework that (i) captures PESTEL factors influencing the implementation of passive ecological restoration in páramo ecosystems as a measure of NbS and (ii) assesses its associated environmental impacts. Our approach integrates a scoping review with remote sensing techniques, water quality assessment, and correlation analyses. Focusing on the Upper Pita and Upper Cutuchi River Basins-key water sources for Andean communities in Ecuador, we reveal that the deterioration of their páramo ecosystems in the 20th century was mainly due to camelid grazing and pine timber production. In response to these threats, bottom-up management efforts starting in 1999, guided by various PESTEL factors, promoted policies, regulations, social agreements, and financial support for achieving passive ecological restoration between 2010 and 2017 in the Upper Pita River Basin. As a result, the conservation of 73.4% of natural páramo with excellent water quality in 2022. By contrast, top-down management in the Upper Cutuchi River Basin was ineffective because national strategies failed to tackle the local environmental challenges posed by the PESTEL factors. Hence, only 31.6% of the natural páramo remained with poor water quality by 2022. Our study is the first to demonstrate that passive ecological restoration benefits these ecosystems, while its absence results in significant changes that require additional restoration strategies.
Keywords: ddc:630